Experience in developing the science, technology and innovation development strategy towards 2030, and implications for developing a mid-term plan for implementing the strategy during the 2026-2030 period - Ha Cong Hai; Nguyen Manh Tien (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Summary: Experience from countries around the world shows that strategy development in general, and science, technology and innovation (STI) strategy development in particular, the strategy development process and method are considered decisive factors for the quality and feasibility of strategy development documents. There is no common or one-size-fits-all process and method for developing the STI strategy development to apply to all countries, but it depends on the conditions, context, and strategy development tradition of each country. The article focuses on analyzing the practical process and methods of developing the Science, technology and innovation Development Strategy for 2030 in Vietnam, drawing lessons from experience, and suggesting implications for developing the Science, technology and innovation Development Plan for the period 2026 - 2030. Code: 21112101